Electronic cigarette and tobacco use in individuals entering methadone or buprenorphine treatment. (1st April 2019) - Baldassarri, Stephen R.; Fiellin, David A.; Savage, Mary Ellen; Madden, Lynn M.; Beitel, Mark; Dhingra, Lara K.; Fucito, Lisa; Camenga, Deepa; Bollampally, Pooja; Barry, Declan T.
Highlights: Most people with opioid use disorder (OUD) are also addicted to cigarette smoking. 62% of OUD patients reported electronic cigarette (EC) use history. Daily EC use was associated with higher odds of being a former smoker. Interventions using ECs may be effective to help reduce harms and mortality in OUD. Abstract: Background: Although smoking is prevalent among populations with opioid use disorder (OUD), few studies have examined electronic cigarette (EC) use in individuals seeking opioid agonist therapy (OAT). The aim of this study was to evaluate the prevalence and correlates of EC use among individuals seeking OAT. Methods: 782 patients seeking OAT for OUD completed surveys assessing current and past EC use, reasons for use, current and past cigarette smoking, nicotine dependence, psychiatric distress, trauma, and pain. Bivariate and multivariate models evaluated correlates of daily EC use, past-30-day EC use, and current cigarette smoking. Results: 6% of patients reported daily EC use, 18% reported past-30-day use, 62% reported EC use history, and 85% reported current cigarette smoking. 46% reported using ECs to quit or cut down smoking. In multivariate analyses, daily EC use was associated with higher odds of being a former smoker (OR 21; CI 1.7–273) and lower odds of ever smoking more than 100 cigarettes (OR 0.07; CI 0.01–0.32), while EC use in the past 30 days was associated with lower odds of being Caucasian (OR 0.55; CI 0.34–0.89), ever smoking more than 100 cigarettes (OR 0.13; CI 0.02–0.67), and history of chronic pain (OR 0.59; CI 0.38-0.90), and higher odds of reporting psychiatric distress (OR 1.5; CI 1.1–2.2). Conclusions: EC use is common among people with OUD who smoke cigarettes. Those with daily use had higher odds of being former smokers than current smokers. Interventions using ECs may be effective to help reduce harms and mortality in OUD.